Training- and sex related alterations of global feature-tracking strain values of highly trained athletes using cardiac magnetic resonance imaging. (14th October 2021) - Szabo, L; Juhasz, V; Dohy, Z; Czimbalmos, C; Kiss, O; Sydo, N; Szucs, A; Kiss, A R; Suhai, F I; Toth, A; Merkely, B; Vago, H
Abstract: Introduction: Cardiac magnetic resonance imaging (CMR) is a reference method for assessing the morphological and functional parameters of the heart, and more recently, strain analysis can detect mechanical features. Based on echocardiographic data, strain parameters may help to differentiate between physiological athlete adaptation and pathological hypertrophy, however, there are still little data available among elite athletes regarding strain values using CMR. Aims: Our aim was to study the strain characteristics of the athlete's heart using CMR imaging. Methods: Overall, 228 (149 male, 24±5 years) highly trained adult (18–35 years), Caucasian athletes (≥10h training hours/ week) who underwent CMR examination as part of their screening were included in our study. Cine movie images in long- and short axis views were performed. Standard CMR parameters including left- and right ventricular (LV and RV) volumes, ejection fraction and muscle masses were measured. Feature-tracking strain analyses were performed, global LV longitudinal, circumferential and radial strain and RV longitudinal strain were calculated. CMR parameters of athletes were compared with healthy sex- and age matched sedentary control groups (n=105, 55 men). Results: Athletes competed in mixed (n=99), endurance (n=99) and power (n=30) sport disciplines, and performed sport activity in quite high training hours (average: 21±5 hours/week). Regarding standard CMR parameters we found pronounced sports adaptation in both male and female athletes compared to sex- and age matched controls including lower LV and RV ejection fraction (p<0.05), elevated LV and RV volumes and masses (p<0.001). Strain analysis also revealed differences between athletes and controls: LV- GLS, GCS, GRS were lower in athletes compared to controls, regardless of their sex (p<0.05). RV-GLS was slightly lower in male athletes compared to male controls. Examining the effects of sport disciplines, we found the most marked sport adaptation in the case of endurance athletes. Training hours showed a positive correlation with LV-GLS and GCS values, and a negative correlation with GRS (p<0.001). We found that male athletes had more pronounced cardiac adaptation compared to females (p<0.001), and their LV-GLS and GRS values were lower (GLS: male athletes: −20±2% vs. female athletes: −22±2%; p<0.001), while GCS and RV-GLS showed no difference between sexes. Conclusion: Our results suggest that in addition to standard CMR parameters, global strain values also show a small but consistent change during sport adaptation. Moreover, our results support the use of sex specific strain normal values in highly trained athletes. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The study was financed by the Research Excellence Programme of the Ministry for Innovation and Technology in Hungary within the framework of the Bioimaging Thematic Programme of Semmelweis University. LS was supported by the ÚNKP-20-3-II-SE-61 New National Excellence Program of the Ministry for Innovation and Technology from the source of the National Research, Development and Innovation Fund.